Methanotroph-methylotroph lipid adaptations to changing environmental conditions - Richter, Nora; Villanueva, Laura; Hopmans, Ellen C.; Bale, Nicole J.; Sinninghe Damsté, Jaap S.; Rush, Darci (Frontiers in Microbiology, 2025)
Methanotrophs, in particular methane-oxidizing bacteria (MOB), regulate the release of methane from lakes, and often co-occur with methylotrophs that may enhance methane-oxidation rates. Assessing the interaction and physiological status of these two microbial groups is essential for determining the microbial methane buffering capacity of environmental systems. Microbial membrane lipids are commonly used as taxonomic markers of specific microbial groups; however, few studies have characterized the changes of membrane lipids under different environmental conditions. For the case of methane-cycling microorganisms, this could be useful for determining their physiological status and potential methane buffering capacity. Here we investigated the changes in membrane lipids, bacteriohopanepolyols (BHPs) and respiratory quinones, produced by MOB and methylotrophs in an enrichment co-culture that primarily consists of a methanotroph (Methylobacter sp.) and a methylotroph (Methylotenera sp.) enriched from a freshwater lake under different methane concentrations, temperatures, and salinities. To assess whether the lipid response is similar in methanotrophs adapted to extreme environmental conditions, we also characterize the BHP composition and respiratory quinones of a psychrotolerant methanotroph, Methylovulum psychrotolerans, isolated from an Arctic freshwater lake and grown under different temperatures. Notably, in the Methylobacter-Methylotenera enrichment the relative abundance of the BHPs aminobacteriohopanepentol and aminobacteriohopanepolyols with additional modifications to the side chain increased at higher temperatures and salinities, respectively, whereas there was no change in the distribution of respiratory quinones. In contrast, in the Methylovulum psychrotolerans culture, the relative abundance of unsaturated BHPs increased and ubiquinone 8:8 (UQ8:8) decreased at lower temperatures. The distinct changes in lipid composition between the Methylobacter-Methylotenera enrichment and the psychrotolerant methanotroph at different growth temperatures and the ability of the Methylobacter-Methylotenera enrichment to grow at high salinities with a singular BHP distribution, suggests that methane-cycling microbes have unique lipid responses that enable them to grow even under high environmental stress.